(untitled) (Nucleus, 2016)
This study estimated the burden of alcohol use in Disability-Adjusted Life Years (DALY) for Brazil. The measures of DALY combines the measures of Years of Life Lost (YLL) and Years Lived with Disability (YLD), based on methodology of the Global Burden of Disease (GBD) and were presented using the rate of 1:10,000. Alcohol use was defined by ICD-10 F10-F10.9. We used outpatient treatment, admissions and mortality data and the disability weights specific for alcohol according with GBD to calculate the DALY-relevant measures. The total value of DALY in Brazil due to the alcohol use was 32.05, similar to what we observed in YLD total value [31.60] and different of the measure of the YLL total value [0.45]. There is important difference in DALY’s value between gender, being the biggest at the age group 40-44 [158.10 male and 34.03 female]. The biggest loss of DALY’s total value is at the 44 age group with 158.01 years. The impact of the DALY due to alcohol use represents the need to refine existing actions in prevention and treatment, seeking the search for better strategies that promote more responsible alcohol use and decrease individual and social harms.